Notes about happiness and the science - Fortunato, Ivan (Revista Hipótese, 2018)
The purpose of this manuscript is to present some reflections about Happiness from an interdisciplinary point of view. Written in the form of an essay, it seeks to relate elements from the scientific literature with some knowledge produced by the arts (mainly music, literature and cinema) and the common sense. It can be said that the text is inconclusive; after all, it is only intended to conjecture about the sense of being happy.
Keywords: Happiness; Art; Science; Interdisciplinarity